Pengaruh Kepemimpinan Toxic dan Situasi kerja Terhadap Kinerja Karyawan di Mediasi oleh Employee performance Karyawan Pada UPT Latihan Kerja Pasuruan - Zaenal Arifin; Siti Mujanah; Achmad Yanu Alif Fianto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
One of the things that can improve employee performance is employee job satisfaction. This study investigates the effect of toxic leadership and work situations on employee satisfaction. It also investigates whether employee satisfaction is a good mediator. This study conducted a survey on employees at UPT Balai Latihan Kerja Pasuruan. Using saturated sampling method, 42 employees. The data was then analyzed using Structural Equation Modeling. The findings show that toxic leadership and work situations contribute positively to employee satisfaction. The study also proved that employee satisfaction mediates the relationship between toxic leadership and work situations on employee performance. This study contributes to understanding employee behavior using the framework of employee satisfaction and employee performance in Balai Latihan Kerja companies, which can also be applied to other general companies.